Distinct Whole‐Body Movements in Response to Alcohol and Sexual Content in Alcohol Use Disorder. (28th February 2021) - Noël, Xavier; Dubuson, Macha; Rougier, Marine; Lelard, Thierry; Mouras, Harold; Kornreich, Charles; Wyckmans, Florent; Pereira, Maylis; Chatard, Armand; Jaafari, Némat; Campanella, Salvatore
Abstract : Background: Spontaneous motor responses of approach and avoidance toward stimuli are important in characterizing psychopathological conditions, including alcohol use disorder (AUD). However, divergent results have been reported, possibly due to confounded parameters (e.g., using a symbolic vs. a sensorimotor task, implementation of approach–avoidance as a measure vs. a manipulation). Methods: We studied whole‐body/posturometric changes by using a sensorimotor measure relying on embodied cognition principles to assess forward (approach) and backward (avoidance) spontaneous leaning movements. Over a 12‐second period, 51 male patients with AUD and 29 male control participants were instructed to stand still in response to both alcohol and sexual visual content. Patients with AUD were then divided into "abstainers" and "relapsers, " depending on their continuous abstinence at 2 weeks postdischarge (obtained via a telephone follow‐up interview). The effects of the group, the stimulus type, the experimental period, and their interactions on the posturometric changes were tested using mixed Analyses of variance (ANOVAs), with a significance threshold set at 0.05. Results: Contrary to our expectations, patients and controls did not show significant difference in their forward/backward micromovements while passively viewing alcohol or sexual content ( p  > 0.1). However, in line with our hypothesis, patients who relapsed several weeks following discharge from the rehabilitation program were significantly more reactive and more likely to lean back during the first seconds of viewing alcohol cues ( p  = 0.002). Further, "relapsers" were more likely to lean forward during exposure to sexual content than participants who remained abstinent ( p  < 0.001). Conclusions: Among individuals with AUD, there are distinct pattern of spontaneous movements that differentiate "abstainers" and "relapsers, " findings that can be understood in light of existing data and theories on action tendencies. Abstract : Spontaneous reactions to emotional stimuli help characterize conditions such as alcohol use disorder (AUD). We assessed forward (approach) and backward (avoidance) spontaneous leaning movements in AUD patients responding to both alcohol and sexual visual content. While AUD patients showed similar movements to controls, we observed distinct patterns of movements between patients who relapsed several weeks later and those who remained abstinent. Relapsers were more likely to lean back in response to alcohol cues and lean forward when viewing sexual content.